Try NerdPal! Our new app on iOS and Android

# Solve the equation $2\left(\frac{x-1}{3}\right)+2=6+x$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$x=-14$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$2\frac{x-1}{3}+2=6+x$

Specify the solving method

1

Multiplying the fraction by $2$

$\frac{2\left(x-1\right)}{3}+2=6+x$

Learn how to solve one-variable linear equations problems step by step online.

$\frac{2\left(x-1\right)}{3}+2=6+x$

Learn how to solve one-variable linear equations problems step by step online. Solve the equation 2(x-1)/3+2=6+x. Multiplying the fraction by 2. We need to isolate the dependent variable x, we can do that by subtracting 2 from both sides of the equation. Multiply the single term 2 by each term of the polynomial \left(x-1\right). Multiply both sides of the equation by 3.

$x=-14$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$2\frac{x-1}{3}+2=6+x$